2000
DOI: 10.1002/(sici)1097-0223(200002)20:2<144::aid-pd770>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Inherited interstitial deletion of chromosomes 5p and 16q without apparent phenotypic effect: further confirmation

Abstract: We describe two families in which an inherited interstitial deletion is present without apparent associated phenotypic abnormalities. The first deletion was discovered in a 19-year-old male with a previously diagnosed peroxisomal disorder. High-resolution chromosome analysis was interpreted as 46,XY,del(5)(p14.1p14.3). The patient's phenotypically normal mother had the same interstitial deletion. Chromosome 5p14 deletion has been reported in a three-generation family without phenotypic anomalies. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
(21 reference statements)
2
20
0
Order By: Relevance
“…Recently, Johnson et al 47 reported a healthy father and an affected son (microcephaly, seizures, and global developmental delay) with an identical interstitial deletion of 5p14. Hand et al 48 also reported a family in which a patient with a peroxisomal disorder and his normal mother had the same interstitial deletion in 5p14. It is possible that the phenotypic effect of the haploinsufficiency may depend on the presence of recessive alleles on the homologous chromosome or genetic background or both.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Johnson et al 47 reported a healthy father and an affected son (microcephaly, seizures, and global developmental delay) with an identical interstitial deletion of 5p14. Hand et al 48 also reported a family in which a patient with a peroxisomal disorder and his normal mother had the same interstitial deletion in 5p14. It is possible that the phenotypic effect of the haploinsufficiency may depend on the presence of recessive alleles on the homologous chromosome or genetic background or both.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the Barber 2000Overhauser et al 1986Hand et al 2000Mascarello et al 1991Reddy 1999Batanian et al 2001Pelly et al 1992Davis et al 1999Barber et al 1991Li et al 2002Couturier et al 1985Hand et al 2000Witt et al 1988Rigola et al 2001 Duplication 1p21-p31 1q11-q22* 1q42.11-q42.12* 3q25-q25* 3q28-q29 4q31.3-q33* 5q15-q21* 6q24. Zaslav et al 1993Chan et al 2002Bortotto et al 1990Fryburg et al 1994Millard et al 1998Maltby et al 1999Li et al 1998Barber 2000Chan et al 2003Engelen et al 2000Harada et al 2002Stumm et al 2002Di Giacomo et al 2004Saxe et al 2003Robin et al 1997Cook et al 1997Wolff et al 1991 recorded cases are presented in Table 1 (after Barber).…”
Section: Unbalanced Euchromatic Abnormalities (Ubcas) Deletionsmentioning
confidence: 99%
“…Novel benign variants are still being uncovered. Polymorphisms may extend several megabases (and thus multiple array loci) (Hand et al 2000;Martin et al 2002;Starke et al 2003). Not surprisingly, at the higher resolution level obtained by molecular karyotyping, similarly polymorphic loci are detected and, due to the higher resolution, the number of variants that are observed has equally increased.…”
Section: Parameters Influencing Array Cgh Qualitymentioning
confidence: 99%